The estimation of economic benefits of urban trees using contingent valuation method in Tasik Perdana, Kuala Lumpur - Yeo, Sok Cheng; Abd. Ghani, Awang Noor; Lee, P. C. (Universiti Putra Malaysia Press, 2013)
Urban trees provide a multitude of tangible and intangible services which include provisionary, regulatory, as well as cultural and support services to the community. Unfortunately, to set a monetary value on these said services is challenging to say the least. Ignorance of such monetary value is unintentional and this is mainly due to the lack of awareness and the absence of monetary value of the services itself. Hence, the quality of these urban trees degrades over time as no one appreciates its monetary value. In light of this situation, a study was initiated to determine the economic benefits of the urban trees that were planted surrounding Tasik Perdana (TP) area. For this purpose, a total of 313 respondents were interviewed in the TP area using the contingent valuation method (CVM). The objective of this study was to elicit willingness to pay (WTP) for these urban trees. WTP represents the willingness of a person to pay in monetary terms to secure and sustain these urban trees. Hence, seven bid prices were used and distributed to the respondents: RM1.00, RM5.00, RM10.00, RM15.00, RM20.00, RM25.00 and RM30.00. Logit and linear regression models were applied to predict the maximum, mean, and median WTP. The study concludes that the estimated mean WTP is RM10.32 per visit and the estimated median WTP is RM10.08 per visit.